Detecção sorológica e molecular do Cassava common mosaic virus em mandioca na região noroeste do Paraná - Silva, Jaqueline Manzatti da (2011)
: The Cassava common mosaic virus (CsCMV) is considered to be more frequent in central and south of Brazil producing areas. From this perspective, the objective of this work was to detect and identify a virus in cassava plants from in vitro micropropagation, and collected in producing areas of Paranavaí, northwest of Paraná, using serological and molecular methods. Indirect-PTA-ELISA tests were used to test cassava leaves in 1/300 dilution, using a polyclonal antiserum specific for CsCMV diluted 1/10.000. From 65 samples obtained by micropropagation, 10 were healthy tested. The serological tests showed that one out of 61 samples from the producing region of Paranavaí was free of the virus. Of the 20 samples from the UEM germplasm collection, five were free of the virus. The same samples were also tested through immunocapture (IC-RT-PCR). The cassava leaves were diluted 1/10 and tested using a purified IgG specific for CsCMV. From the 16 samples identified as virus-free by indirect-PTA-ELISA, and later tested by IC-RT-PCR, 10 showed infected by the virus. Of the five plants that had presented resulted negative for the PTA-ELISA-indirect one, all had shown resulted positive for the IC-RT-PCR. Five out of 10 plants from the in vitro micropropagation were free of the virus. From 61 samples collected in Paranavaí field areas, only one was virus free as confirmed by indirect-PTA-ELISA and IC-RT-PCR. To confirm the identity of the virus detected by IC-RT-PCR, the amplified PCR products were cloned and sequenced. Comparing the obtained nucleotide sequences with those of other Potexvirus from GenBank, it was found 87% identity with a sequence of CsCMV, confirming the virus detected in this work represents a strain of Cassava common mosaic vírus.